Relay suitability based routing protocol for video streaming in vehicular ad-hoc network - Omar Abdulmaged, Hammood (2022)
Video streaming in Vehicular Ad Hoc Networks (VANETs) can be utilize for roadside emergency and smart video surveillance services. Vehicular networking has emerged with advanced wireless technology concepts that support safety messaging, route condition updates, and real-time video traffic information sharing. However, the provision of scalable video streaming that meets the stringent video quality without video distortions under a highly dynamic network topology is a challenging task. In a high-density network, the transfer packet are prone to collision, especially under a unicast routing protocol. The potential solution to the aforementioned problems is the development of a technique that can guarantee QoS. This problem can be solve by efficiently selecting the suitable relay nodes for communication performance in the VANET environment. This thesis proposed a solution technique referred to as an Enhanced Transmit Packet Coding (enhanced-TPC) and weighted division algorithm (WDA) in Relay suitability-based routing protocol (RESP) term as WDA-RESP. In the RESP, this protocol takes routing decisions based on vehicle proximity to the destination, the expected transmission count (ETX), density-aware collision probability, and relative velocity-based link stability measurement. The RESP estimates the geographic advancement and link stability of a vehicle towards its destination in the small region. Additionally, to ensure reliability the RESP incorporate WDA to selects high-quality forwarding node for video streaming. The second technique for improving VANET video quality is using Transmit Packet Coding (TPC). Here, the relay suitability metric integrates the suitable parameters in the network coding and selects a high-quality forwarding node for video streaming. The experimental results of the WDA-RESP outperformed Lifetime-aware Beacon-less Routing Protocol (LBRP) and other traditional geographical streaming protocols in which WDA-RESP provide high packet delivery ratio and less packet delay for video streaming. In the TCP experiment, the results show superiority of enhanced-TCP when compared to the existing techniques in terms of throughput, latency, hop delay, packet delivery ratio, network decoder outage probability, and block error rate. In conclusion, the RESP provided a scalable unicast geographic routing protocol for video streaming in VANETs and improved video dissemination processes and with a probability of γ = 50%, it was the best solution compared to flooding, 25% effective toward scalability and 75 % towards balancing video QoS parameters like reliability, connectivity, packet loss, and delay within vehicular environments. Also, the TPC ensures that the number of transmitted packets over the network can be reduced while providing an efficient utilization of network devices and resources. It is evident from the result that the proposed algorithm able to produced better result.